(3GbJUGOjGJ GdYGde GdGSdGej (B:s (3GdhGbY h GdeQJLi (B/s - (3eMehO MSjf, hLOjs ((3GdGScfOQjI(B: s (3efTCI GdeYGQa(B, s, 1994)
(3JYQja h fWGb GdYGde GdGSdGej eY OQGSI GdNUGFU GdCSGSjI dGbJUGOjGJg h gjGcd GdGfJGL ajg , GbJUGOjGJ GdYGde GdGSdGej aj aJQI EROgGQg JGQjNjG eY CHQR GdGecGfjGJ h GdehGQO GdGbJUGOjI ddYGde GdGSdGej h GhVGY h JhLgGJ bWGYGJ GdGfJGL GdQFjSjI aj GdhWf GdGSdGej , GdYdGbGJ GdGbJUGOjI ddYGde GdGSdGej eY GdNGQL , GdJcGed GdGbJUGOj Hjf GdOhd GdGSdGej (B: (3VQhQJg hhGbYg h eJWdHGJ fLGMg , CQcGf h OYGeGJ GdJcGed h GdJYGhf GdGbJUGOj Hjf GdOhd GdGSdGejI , GdJYGhf GdJehjdj Hjf GdHdOGf GdGSdGejI (B.s
Keywords: (3GdGbJUGOs; (3GdEbJUGO GdESdGejs; (3GdJfejI GdEbJUGOjIs